Influence of Foundation Ground Material Stiffness on Structural Design Parameters of Culvert Foundations (International Journal of Scientific Research in Science and Technology, 2025)
Soil-structure interaction constitutes a pivotal consideration in the analysis and design of any infrastructure resting on the ground. The type of ground material on which the foundation rests have significant influence in the structural design of foundation of any structures. Three different ground material, namely medium dense soil, very soft rock or hard soil and rock with moderate jointing have been considered representing three distinct foundation materials to study the influence of changing stiffness of the foundation resting ground materials on important design parameters such as moment and shear. While a culvert serves as the model for this study, the primary focus lies on the foundation, specifically the base slab, as soil-structure interaction predominantly influences this component. Furthermore, this study places particular emphasis on characterizing the interaction between the supporting structure and the ground through the adoption of different modelling techniques. Simplified spring model, subsequently compared with an elastic continuum model, which is posited as the reference or "correct" solution within this investigation. Alternative approaches, such as employing the concept of static equilibrium, will also be subject to evaluation and comparative analysis alongside the aforementioned methodologies. The study revealed that increasing the stiffness of the ground material results in a reduction in stress along the structure’s foundation. This indicates that ground material stiffness significantly influences foundation stress calculations. This conclusion is based on the results from three distinct modeling techniques. Furthermore, the findings suggest that significant design optimizations can be achieved by adopting the elastic continuum model over the simplified spring model and the static equilibrium method.